Simplifying
x + 9 = 18 + -2x
Reorder the terms:
9 + x = 18 + -2x
Solving
9 + x = 18 + -2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '2x' to each side of the equation.
9 + x + 2x = 18 + -2x + 2x
Combine like terms: x + 2x = 3x
9 + 3x = 18 + -2x + 2x
Combine like terms: -2x + 2x = 0
9 + 3x = 18 + 0
9 + 3x = 18
Add '-9' to each side of the equation.
9 + -9 + 3x = 18 + -9
Combine like terms: 9 + -9 = 0
0 + 3x = 18 + -9
3x = 18 + -9
Combine like terms: 18 + -9 = 9
3x = 9
Divide each side by '3'.
x = 3
Simplifying
x = 3